Association between vitamin A and asthma: A meta-analysis with trial sequential analysis - Hu, Jun; Sang, Jiajia; Hao, Feng; Liu, Li (Frontiers in Pharmacology, 2023)
Abstract Objective: To explore the association between vitamin A (vit A) status and risk of asthma. Methods: PubMed, Web of Science, Embase and the Cochrane Library were electronically searched to identify related studies that reported the association between vit A status and asthma. All databases were searched from inception to November 2022. Two reviewers independently screened literature, extracted data, and assessed risk bias of included studies. Meta-analysis was performed on R software Version 4.1.2 and STATA Version 12.0. Results: A total of 17 observational studies were included. A pooled analysis showed that the serum vit A concentrations in patients with asthma was lower than that in healthy controls (SMD= -2.479, 95% CI: -3.719, -1.239, 95% PI: -7.510, 2.552), and relatively higher vit A intake in pregnancy was associated with an increased risk of asthma at age 7 years (RR=1.181, 95%CI: 1.048, 1.331). No significant correlation was observed between serum vit A levels or vit A intake and the risk of asthma. Conclusion: Our meta-analysis confirms that serum vit A levels are lower in patients with asthma than in healthy controls. Relatively higher vit A intake during pregnancy is associated with an increased risk of asthma at age 7 years. There is no significant correlation between vit A intake and asthma risk in children, nor between serum vit A levels and asthma risk. The effect of vit A may depend on age or developmental stage, diet and genetics. Therefore, further studies are needed to explore the association of vit A and asthma.